HUBUNGAN SOSIAL EKONOMI DAN PERILAKU HIDUP BERSIH DAN SEHAT DENGAN KEJADIAN DIARE PADA BALITA DI DESA BARU KECAMATAN PANCUR BATU - SELAMAT GINTING (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
According to the World Health Organization (WHO) diarrhea is liquid bowel movements more than three times in 24 hours, and focuses more on the consistency of feces than the frequency of defecation. Diarrhea is still one of the main public health problems in Indonesia because of its high morbidity and mortality. This research method is a